2019
DOI: 10.1155/2019/7630894
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA hsa_circRNA_0007334 is Predicted to Promote MMP7 and COL1A1 Expression by Functioning as a miRNA Sponge in Pancreatic Ductal Adenocarcinoma

Abstract: Pancreatic cancer remains one of the leading causes of cancer-related deaths worldwide. Pancreatic ductal adenocarcinoma (PDAC) is the most common type of pancreatic tumor. Many circular RNAs (circRNAs) have proven to play vital roles in the physiological and pathological processes of tumorigenesis; however, their biogenesis in PDAC remains unclear. In this study, the expression profiles of circRNAs from 10 PDAC tissues and their paired adjacent nontumor tissues were analyzed through RNA sequencing analysis. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 48 publications
3
42
0
Order By: Relevance
“…Growing evidence has clarified the fact that circRNAs could serve as the sponges of miRNAs to function in numerous cancers (30,31) and the present research showed that circ-ACACA was mainly expressed in the cytoplasm in NSCLC cells. In this study, miR-1183 was forecasted to be a target of circ-AcAcA and this interaction was confirmed.…”
Section: Discussionsupporting
confidence: 51%
“…Growing evidence has clarified the fact that circRNAs could serve as the sponges of miRNAs to function in numerous cancers (30,31) and the present research showed that circ-ACACA was mainly expressed in the cytoplasm in NSCLC cells. In this study, miR-1183 was forecasted to be a target of circ-AcAcA and this interaction was confirmed.…”
Section: Discussionsupporting
confidence: 51%
“…Remodelling of the ECM and angiogenesis in cancer stroma can be considered part of the tumour invasion processes. Circ-0007334 regulates MMP-7 and collagen type I alpha 1 chain (COL1A1) by competitively adsorbing miR-144-3p and miR-577 to enhance the expression and functions of MMP-7 and COL1A1 in pancreatic ductal adenocarcinoma (PDAC) [122]. COL1A1 is responsible for encoding ECM remodelling-related collagens, which are the most abundant proteins in the ECM.…”
Section: Remodelling Of the Extracellular Matrix (Ecm)mentioning
confidence: 99%
“…MMP7 and MMP26 are the only two members of the matrilysin subfamily. A large number of studies have compared MMP7 expression in PDAC patients with pancreatitis patients and/or healthy controls and have consistently shown that MMP7 levels are elevated in PDAC patients (Table 1) [34][35][36]54,69,91,[97][98][99][100][101][102][103][104]. More importantly, MMP7 levels correlate with metastasis and/or survival in most, but not all, studies.…”
Section: Matrilysins In Pdacmentioning
confidence: 99%